On-Line Gaseous Formaldehyde Detection Based on a Closed-Microfluidic-Circuit Analysis - Anaïs Becker; Christina Andrikopoulou; Pierre Bernhardt; Claire Trocquet; Stéphane Le Calvé (Chemosensors, 2020)
This paper describes a compact microfluidic analytical device in a closed-circuit developed for the detection of low airborne formaldehyde levels. The detection is based on the passive trapping of gaseous formaldehyde through a microporous tube into the acetylacetone solution, the derivative reaction of formaldehyde with acetylacetone to form 3,5-Diacetyl-1,4-dihydrolutidine (DDL) and the detection of DDL by fluorescence. The recirculation mode of the analytical device means that the concentration measurement is carried out by quantification of the signal increase in the liquid mixture over time, the instantaneous signal increase rate being proportional to the surrounding gaseous formaldehyde concentration. The response of this novel microdevice is found to be linear in the range 0–278 µg m−3. The reagent volume needed is flexible and depends on the desired analytical resolution time and the concentration of gaseous formaldehyde in the environment. Indeed, if either the gaseous concentration of formaldehyde is high or the reagent volume is low, the fluorescence signal of this recirculating liquid solution will increase very rapidly. Consequently, the sensitivity simultaneously depends on both the reagent volume and the temporal resolution. Considering a reagent volume of 6 mL, the hourly and daily detection limits are 2 and 0.08 µg m−3, respectively, while the reagent autonomy is more than 4 days the airborne formaldehyde concentration does not exceed 50 µg m−3 as it is usually the case in domestic or public indoor environments.